Full-Duplex Self-Recovery Optical Fibre Transport System Based on a Passive Single-Line Bidirectional Optical Add/Drop Multiplexer - Chung-Yi Li; Ching-Hung Chang; Dong-Yi Lu (IEEE Photonics Journal)
A full-duplex self-recovery optical fibre transport system is proposed on the basis of a novel passive single-line bidirectional optical add/drop multiplexer (SBOADM). This system aims to achieve an access network with low complexity and network protection capability. Polarisation division multiplexing technique, optical double-frequency application and wavelength reuse method are also employed in the transport system to improve wavelength utilisation efficiency and achieve colourless optical network unit. When the network comprises a hybrid tree–ring topology, the downstream signals can be bidirectionally transmitted and the upstream signals can continuously be sent back to the central office in the reverse pathways due to the remarkable routing function of the SBOADM. Thus, no complicated optical multiplexer/de-multiplexer components or massive optical switches are required in the transport system. If a fibre link failure occurs in the ring topology, then the blocked network connections can be recovered by switching only a single optical switch preinstalled in the remote node. Simulation results show that the proposed architecture can recover the network function effectively and provide identical transmission performance to overcome the impact of a breakpoint in the network. The proposed transport system presents remarkable flexibility and convenience in expandability and breakpoint self-recovery.